2020
DOI: 10.3390/molecules25225320
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Polymers’ Foaming and Blends with Organic Foaming-Aid Structured Additives in Supercritical CO2, a Way to Fabricate Porous Polymers from Macro to Nano Porosities in Batch or Continuous Processes

Abstract: Organic polymers can be made porous via continuous or discontinuous expansion processes in scCO2. The resulting foams properties are controlled by the interplay of three groups of parameters: (i) Chemical, (ii) physico-chemical, and (iii) technological/process that are explained in this paper. The advantages and drawbacks of continuous (extrusion, injection foaming) or discontinuous (batch foaming) foaming processes in scCO2, will be discussed in this article; especially for micro or nano cellular polymers. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 92 publications
1
23
0
Order By: Relevance
“…There are many works associated with TPS, such as the study of starch-based films [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], the production of innovative biodegradable products [ 29 ], the additives used to strengthen TPS [ 30 ], water or azodicarbonamide used as foaming agents to develop starch-based foams [ 18 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and evaluating the performance of starch loose-fill foams and expanded polystyrene [ 39 ]. Foam products are often used in packing goods, which can easily become plastic garbage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many works associated with TPS, such as the study of starch-based films [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], the production of innovative biodegradable products [ 29 ], the additives used to strengthen TPS [ 30 ], water or azodicarbonamide used as foaming agents to develop starch-based foams [ 18 , 26 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and evaluating the performance of starch loose-fill foams and expanded polystyrene [ 39 ]. Foam products are often used in packing goods, which can easily become plastic garbage.…”
Section: Introductionmentioning
confidence: 99%
“…Starches with high amylose content are able to produce TPS foams [ 18 , 26 , 31 , 32 , 35 , 36 , 38 ]. Starch grafting by poly(methyl acrylate) [ 34 ], or grafting polystyrene [ 37 ] using water as a foaming agent to make foams, has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…It was also exploited for designing nonisocyanate polyurethanes (NIPUs) foams as promising alternatives to conventional PU foams for thermal insulation. [52] Despite the numerous advantages of this method used for foaming many polymer matrices, [39,40,53,54] it does require intricate equipment to maintain CO2polymer melt under pressure. Moreover, the method is hardly transferrable to crosslinked polymers, i.e., thermosetting polymers.…”
Section: General Introductionmentioning
confidence: 99%
“…On the other hand, in a PMMA/20 wt.% MAM blend, through a quasi-one-step batch foaming, a "porous to nonporous" transition was observed on thick samples. Such a sharp porosity gradient (from nonporous transparent areas to porous opaque areas within the same sample) revealed a lower pore size limit of around 50 nm in a classical batch process in "mild conditions" [10]. Qingfeng et al reported a remarkable increase in the cell density of PP foams with the inclusion of a 5.2 wt.% of PDMS [5].…”
Section: Introductionmentioning
confidence: 99%